Fermentation as an Alternative Process for the Development of Bioinsecticides - Alejandra B. Omarini; Fernanda Achimón; Vanessa D. Brito; Julio A. Zygadlo (Fermentation, 2020)
Currently, insect pest control is carried out through the application of synthetic insecticides which have been related to harmful effects on both human and environmental health, as well as to the development of resistant pest populations. In this context, the development of new and natural insecticides is necessary. Agricultural and forestry waste or by-products are very low-cost substrates that can be converted by microorganisms into useful value-added bioactive products through fermentation processes. In this review we discuss recent discoveries of compounds obtained from fermented substrates along with their insecticidal, antifeedant, and repellent activities. Fermentation products obtained from agricultural and forestry waste are described in detail. The fermentation of the pure secondary metabolite such as terpenes and phenols is also included.